Screen-based sedentary behaviours in Italian school children: the ZOOM8 study - Myriam Galfo; Laura D'Addezio; Laura Censi; Romana Roccaldo; Giordano Giostra (Epidemiology, Biostatistics and Public Health)
<!--[if gte mso 9]> Normal 0 14 <![endif]--> Background: screen-based sedentary behaviours likely have a negative impact on many aspects of youth health and development. The purpose of this study was to describe the screen-based sedentary behaviours and to examine factors associated in a sample of Italian school children. Methods: 2129 children, aged 8-9 years, from the three main geographical areas of Italy were involved. Body weight and height were measured. Screen-based sedentary behaviours were evaluated using a parent-reported questionnaire that included items about the time spent watching television (TV) and using computer/playstation and other electronic games. Pearson’s chi-square test and logistic regression analysis were conducted to study possible associated factors. Results: more time was spent in screen-based sedentary activities during non-school days rather than on school days. More males than females watched television more than the recommended 2 hours a day and spent the same time using computer (PC), playstation and other electronic games. The presence of a TV in the child’s bedroom was significantly associated with geographical area, and inversely associated with mother’s education. Moreover, children with a TV in the bedroom had higher odds of being overweight/obese and watching TV more than 2 hours a day than those without a TV. According to multiple logistic regression gender, mother’s age and mother’s education were predictors of the total screen time. Conclusions: Italian children spent a significant amount of time in screen-based sedentary behaviours, exceeding media recommendations. In addition gender, mother’s age and mother’s education were predictors of the total screen time.